Pediatricians' Awareness and Knowledge About Basic Life Support in Turkey - Osman Yeşilbaş; Hasan Serdar Kıhtır (Galenos Yayinevi, 2019)
Introduction:To investigate pediatricians' awareness and knowledge about pediatric basic life support (PBLS) in Turkey.Methods:Pediatric residents of all levels and pediatricians were enrolled in this cross-sectional study. Pediatric emergency and intensive care fellows, specialists, and instructors were excluded. The pediatricians' demographic characteristics, awareness, trainings, and knowledge about PBLS were investigated. A questionnaire was sent to the pediatricians working in different regions of Turkey via e-mail or WhatsApp messaging application.Results:A total of 622 pediatricians participated in this study. 5% of the pediatricians rated their knowledge/skills of PBLS as poor, 37% as moderate, and 58% rated as good. It was found that 26% of the pediatricians had poor, 59% had moderate, and 15% of them had good knowledge of PBLS. 67% of the pediatricians had no awareness of PBLS. There was a significant difference in the average score between participants who have not attended any PBLS course, those who attended a PBLS course in the recent year and those who attended a PBLS course 1-2 years before the study (p<0.001 and p=0.018, respectively). There was no significant difference in average score between pediatricians who have not attended any PBLS course and those who attended a PBLS course 2-3 years, 3-4 years, 4-5 years, and more than 5 years before the study (p>0.05).Conclusion:In our country, pediatricians' awareness and knowledge about PBLS are not sufficient.